2017
DOI: 10.1038/s41598-017-07973-4
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of HIF-1α by siRNA-expressing plasmid delivered by attenuated Salmonella enhances the antitumor effects of cisplatin on prostate cancer

Abstract: Resistance to cisplatin (DDP) and dose-related toxicity remain two important obstacles in the treatment of prostate cancer (PCa) patients with DDP-based chemotherapy. We have investigated whether the knockdown of hypoxia-inducible factor-1 alpha (HIF-1α) by siRNA could enhance the antitumor activity of DDP, and aimed to determine the underlying mechanisms. Intravenous injection of attenuated Salmonella carrying a HIF-1α siRNA-expressing plasmid was used to knockdown HIF-1α in a PC-3 xenograft model. The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…et al, 2012). In addition, in prostate xenografts, the effective downregulation of Hif-1α using salmonella to deliver shRNA-expressing plasmids resulted in increased sensitivity to cisplatin (CDDP) (Gu et al, 2017). However, for the improved drug distribution and response after either TGFβ-or Hif-1α targeting, alternative mechanisms cannot be excluded: TGFβ does not only induce increased ECM build-up and stabilization, but it is also an important regulator of tumor angiogenesis (reviewed in Goumans et al, 2009;van Meeteren et al, 2011).…”
Section: Targeting Tgfβ and Hif1αmentioning
confidence: 99%
“…et al, 2012). In addition, in prostate xenografts, the effective downregulation of Hif-1α using salmonella to deliver shRNA-expressing plasmids resulted in increased sensitivity to cisplatin (CDDP) (Gu et al, 2017). However, for the improved drug distribution and response after either TGFβ-or Hif-1α targeting, alternative mechanisms cannot be excluded: TGFβ does not only induce increased ECM build-up and stabilization, but it is also an important regulator of tumor angiogenesis (reviewed in Goumans et al, 2009;van Meeteren et al, 2011).…”
Section: Targeting Tgfβ and Hif1αmentioning
confidence: 99%
“…Several studies have showed that ELK3 is overexpressed in some cancer cells and correlates with cell migration and invasion [13][14][15]. Hypoxiainducible factor-1α (HIF-1α) can regulate the genes related to cell proliferation, apoptosis, angiogenesis, and metastasis, playing an important role in cancer progression [16][17][18]. Lee et al found that ELK3 expression was upregulated in CD133 + /CD44 + liver cancer stem cells, and silencing of ELK3 attenuated their metastatic potential by regulating HIF-1α expression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, hypoxia-mediated chemoresistance has been regarded as an important obstacle in the development of cancer treatment [ 11 ]. Hypoxia inducible factor-1α (HIF-1α) is an important regulator of transcription in response to hypoxia, which activates the expression of more than 60 target genes involved in cell proliferation, apoptosis, and glycolysis [ 12 ]. It is believed that HIF-1α-induced glycolysis plays a critical role in promoting chemoresistance of NSCLC cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%